Mind‐mindedness and parenting stress in mothers of preterm and full‐term infants: The moderating role of perceived social support. Issue 1 (23rd September 2020) - Suttora, Chiara; Salerni, Nicoletta; Selvagno, Elena; Porro, Matteo; Gangi, Silvana; Squarza, Chiara; Gardon, Laura; Picciolini, Odoardo
ABSTRACT: The goal of this study was to examine the effects of preterm birth and maternal childbirth‐related posttraumatic stress and parenting stress on maternal mind‐mindedness (MM). The study also investigated the effects of perceived social support on parenting stress and MM. Sixty‐five preterm ( N = 32) and full‐term ( N = 33) mother–infant dyads were observed at 6 months. Measures of maternal MM were obtained from observations of mother–infant interaction. Mothers also provided ratings of their posttraumatic stress disorder (PTSD) symptoms, parenting stress, and perceived social support via an online survey. Experiencing a preterm birth did not affect mothers' use of mental state descriptors during mother–infant interaction. Neither childbirth‐related posttraumatic stress nor parenting stress directly affected maternal ability to comment on the child's mental states appropriately. However, at medium and high levels of perceived social support, a negative association between parenting stress and MM was observed. Maternal perception of being emotionally supported by significant others promoted MM in mothers showing low or mild levels of parenting stress, but not in mothers experiencing high stress in parenting their infants. Results suggest that a proclivity to MM might be affected by the interaction between parenting stress and social support, rather than by childbirth‐related variables, such as prematurity. RESUMEN: El propósito de este estudio fue examinar los efectos del nacimiento prematuro y el estrés materno postraumático relacionado con dar a luz, y el estrés de la crianza sobre la disposición de la mente (MM). El estudio también investigó los efectos que la percepción del apoyo social tiene en el estrés de la crianza y la disposición de la mente. Se observaron 65 díadas de madre‐infantes prematuros (N = 32) y de gestación completa (N = 33) a los 6 meses. Las medidas de la disposición mental materna se obtuvieron de observaciones de la interacción madre‐infante. Las madres también suministraron los puntajes de sus síntomas de PTSD, el estrés de la crianza y la percepción del apoyo social por medio de una encuesta electrónica. El experimentar un nacimiento prematuro no afectó el uso por parte de las madres de los factores de descripción del estado mental durante la interacción madre‐infante. Ni el estrés postraumático relacionado con el dar a luz ni el estrés de la crianza directamente afectaron la habilidad materna para comentar de manera apropiada sobre los estados mentales del niño. Sin embargo, al nivel medio y alto de la percepción de apoyo social, se observó una asociación negativa entre el estrés de crianza y la disposición de la mente. La percepción materna de contar con el apoyo emocional de su pareja promovió la disposición mental de las madres que mostraban bajos o leves niveles de estrés de crianza, aunque no así en aquellas madres que experimentaban un nivel alto de estrés en la crianza de sus infantes. Los resultados sugieren que una propensión a la disposición mental pudiera ser afectada por la interacción entre el estrés de crianza y el apoyo social, en vez de las variables relacionadas con el dar a luz, tal como el nacimiento prematuro. RÉSUMÉ: Le but de cette étude était d'examiner les effets du stress posttraumatique lié à la naissance avant terme et à l'accouchement maternel et le stress de parentage sur l'Etat d'esprit/Orientation mentale (abrégé ici EE/OM). L'étude s'est aussi penchée sur les effets du soutien social perçu du stress de parentage et de l'EE/OM maternel. Soixante‐cinq dyades mères‐bébés nés avant terme (N = 32) et à plein terme (N = 33) ont été observées à 6 mois. Les mesures d'EE/FM maternel ont été obtenues d'observations de l'interaction mère‐bébé. Les mères ont aussi offert des évaluations de leurs propres symptômes ESPT, du stress de parentage, et du soutien social perçu au travers d'un questionnaire en ligne. Le fait d'avoir fait l'expérience d'une naissance avant terme n'a pas affecté l'utilisation de descripteurs de santé mentale des mères durant l'interaction mère‐bébé. Ni le stress posttraumatique lié à l'accouchement ni le stress de parentage n'ont affecté directement la capacité maternelle à commenter les états mentaux de l'enfant de manière appropriée. Cependant, à des niveaux moyens et élevés de soutien social perçu, une association négative entre le stress de parentage et l'EE/OM a été observée. La perception maternelle d'être soutenue émotionnellement par leurs partenaires a promu l'EE/FM chez les mères faisant preuve de niveaux bas ou peu élevés de stress de parentage, mais pas chez les mères faisant preuve de stress élevé dans le parentage de leurs bébés. Les résultats suggèrent qu'une tendance à l'EE/OM peut être affectée par l'interaction entre le stress de parentage et le soutien social, plutôt que par des variables liées à l'accouchement, comme la prématurité. ZUSAMMENFASSUNG: Ziel dieser Studie war es, die Effekte von Frühgeburten, geburtsbedingtem mütterlichen posttraumatischem Stress und elterlichem Stress auf mütterliche Mind‐Mindedness (MM) zu untersuchen. Außerdem untersuchte die Studie den Effekt von wahrgenommener sozialer Unterstützung auf elterlichen Stress und MM. 65 Mutter‐Kind Dyaden (mit N = 32 früh und N = 33 reif geborenen Säuglingen) wurden im Alter von 6 Monaten beobachtet. MM wurde anhand von Beobachtungen der Mutter‐Kind‐Interaktion erhoben. Über eine Online‐Umfrage gaben die Mütter ein Rating ihrer PTBS‐Symptome, ihres elterlichen Stresses und ihrer wahrgenommenen sozialen Unterstützung ab. Das Erleben einer Frühgeburt hatte keinen Einfluss auf die Verwendung von Beschreibungen mentaler Zustände durch die Mütter während der Mutter‐Kind‐Interaktion. Weder geburtsbedingter posttraumatischer Stress noch elterlicher Stress hatten einen direkten Einfluss auf die mütterliche Fähigkeit, mentale Zustände des Kindes angemessen zu kommentieren. Bei mittlerer und hoher wahrgenommener sozialer Unterstützung wurde jedoch ein negativer Zusammenhang zwischen elterlichem Stress und MM beobachtet. Wahrgenommene soziale Unterstützung förderte MM bei Müttern mit geringem oder mildem elterlichem Stress, nicht jedoch bei Müttern mit starkem elterlichem Stress. Die Ergebnisse deuten darauf hin, dass eine Tendenz zu MM eher durch die Wechselwirkung zwischen elterlichem Stress und sozialer Unterstützung als durch geburtsbezogene Variablen wie Frühgeburt beeinflusst werden könnte. 抄録: 早期産児と満期産児の母親におけるマインド−マインドネスと育児ストレス:母 親が認識する社会的サポートの緩和的役割 本研究の目的は、母親のマインド−マインドネス(MM)に対する早期産と母親の出 産に関連した心的外傷後ストレスと育児ストレスの影響について研究することで ある。また、育児ストレスとマインド−マインドネスに対する母親が認識する社 会的サポートの影響についても研究した。早期産(N = 32)と満期産(N = 33)の乳 児とその母親 65組を出生後6ヶ月時に観察した。母親のMMの評価は、母子相互作 用の観察から得た。母親らはまた、オンライン調査を通して、PTSD症状、育児ス トレス及び自分が認識する社会的サポートの評価を提供した。早期産の体験は、 母子相互作用中に使われる精神状態の記述子に影響を及ぼすことはなかった。出 産に関連した心的外傷後ストレス及び育児ストレスは、どちらも子どもの精神状 態を適切に表現する母親の能力に直接的に影響を及ぼすことはなかった。しかし ながら、母親が認識する社会的サポートの中及び高レベルにおいて、育児ストレ スとマインド−マインドネス間には負の相関が観察された。重要な他者に精神的 に支援されているという母親の認識は、育児ストレスが低あるいは中レベルでみ られる母親においては、マインド−マインドネスを促進していたが、育児におい て高ストレスを体験している母親ではそうなってはいなかった。結果は、マイン ド−マインドネスの傾向は、早産児といったような出産に関連する変数よりはむ しろ、育児ストレスと社会的サポート間の相互作用によって影響を受ける可能性 を示唆している。 摘要: 本研究旨在探讨早产、母亲分娩相关的创伤后压力和育儿压力对母亲心智 (MM) 的影响。本研究还调查了领悟社会支持对育儿压力和心智的影响。在6个月龄时观察了65个早产 (N = 32) 和足月 (N = 33) 的母婴二人组。从母婴互动的观察中获得了对母亲MM的测量。母亲们还通过在线调查提供了他们的PTSD症状, 育儿压力和领悟社会支持的等级。经历早产并不影响母亲在母婴互动过程中使用心理状态描述词。分娩相关的创伤后压力和育儿压力都不会直接影响母亲对孩子心理状态的恰当评价。但是, 在中等和较高的领悟社会支持水平下, 观察到育儿压力和心智之间呈负相关。在那些表现出较低或中等水平育儿压力的母亲中, 得到另一半情感支持的母性知觉会提高其心智, 但在育儿过程中经历高压力的母亲则不会。研究结果表明, 心智倾向可能会受到育儿压力和社会支持之间相互作用的影响, 而不是受到与分娩相关的变量 (如早产) 的影响。 ملخص: التخاطب الذهني وإجهاد الرعاية الوالدية عند أمهات الأطفال المبتسرين والرضّع كاملي المدى: الدور الملطف للدعم الاجتماعي المتصور كان الهدف من هذه الدراسة هو دراسة آثار الولادة المبتسرة والإجهاد اللاحق للولادة وإجهاد الرعاية الوالدية على التخاطب الذهني الأمومي(MM) .كما بحثت الدراسة في آثار الدعم الاجتماعي المتصور على الإجهاد الأبوي والتخاطب الذهني. تم ملاحظة 65 ثنائي من الأمهات والأطفال المبتسرين (N = 32) وكاملي المدة(N = 33) عند فترة 6 أشهر. تم الحصول على مقاييسMM الأم من ملاحظات التفاعل بين الأم والرضيع. كما قدم الأمهات تقييمات لأعراض اضطراب ما بعد الصدمة، والإجهاد الأبوي، والدعم الاجتماعي المتصور من خلال استبيان على الإنترنت. لم تؤثر تجربة الولادة المبتسرة على استخدام الأمهات لتوصيفات الحالة الذهنية أثناء التفاعل بين الأم والرضيع. لم يؤثر الإجهاد اللاحق للأمومة المرتبط بالولادة أو الإجهاد الأبوي بشكل مباشر على قدرة الأمهات على التعليق على الحالات العقلية للطفل بشكل مناسب. ومع ذلك، لوحظ وجود ارتباط سلبي بين الإجهاد الأبوي والتخاطب الذهني على المستويات المتوسطة والعالية من الدعم الاجتماعي المتصور. وقد عزز تصور الأم للدعم العاطفي من الشريك قدرة التخاطب الذهني لديها وأظهرت مستويات منخفضة أو خفيفة من إجهاد الرعاية الوالدية، ولكن لم يظهر هذا عند الأمهات اللاتي تعاني من الإجهاد العالي في الرعاية الوالدية للرضع. وتشير النتائج إلى أن الميل إلى التخاطب الذهني قد يتأثر بالتفاعل بين إجهاد الرعاية الوالدية والدعم الاجتماعي، وليس بالمتغيرات المرتبطة بالولادة، مثل الولادة المبتسرة.